Metodología basada en cromatografía iónica, absorción atómica y generación de hidruros para determinar selenio en agua potable - Costilla Sánchez, Noé Ildefonso (2008)
In this research an analytical methodology for determining inorganic selenium in samples of drinking water in the city of Trujillo, Peru has been developed. This methodology, developed and validated with a standard solution is based on the techniques of ion exchange chromatography and atomic absorption spectrometry with hydride generation. Using the ionic exchange the alkalinity, was reduced the selenite (SeO32-) and selenate (SeO42-) of the standard solution were pre concentrated and separated. For the atomic sorption spectrometry test, the selenite of the standard solution and solution of sodium borohydride were made to intereact to produce the gas hydride selenium H2Se. The recovery of Se(IV) was 96,9% for Se (IV) and that of Se(VI) 95,1%. The method was successfully validated by determining the parameters: linear range, linearity, accuracy, precision, sensitivity, detection limit, limit of quantification and bias. The application of the method in samples of drinking water from 14 locations in Trujillo, Peru, yielded an average concentration of inorganic selenium of 1,0985 µg / L for Se (IV) and of 0,0883 µg / L for Se (VI).